What Freud really meant : a chronological reconstruction of his theory of the mind - Sugarman, Susan (Cambridge University Press, 2016)
"Through an exacting yet accessible reconstruction of eleven of Freud's essential theoretical writings, Susan Sugarman demonstrates that the traditionally received Freud is the diametric opposite of the one evident in the pages of his own works. Whereas Freud's theory of the mind is typically conceived as a catalogue of uninflected concepts and crude reductionism - for instance that we are nothing but our infantile origins or sexual and aggressive instincts - it emerges here as an organic whole built from first principles and developing in sophistication over time. Sugarman's exciting interpretation, tracking Freud's texts in the order in which he wrote them, grounds his claims in the reasoning that led to them and reveals their real intent. This fresh reading will appeal to specialists and students across a variety of disciplines"--